Analysis of Nurses' Knowledge in Determining Diagnosis of Islamic Spiritual Nursing Care in Sharia Hospitals - Inggriane Puspita Dewi; Nurohmah Suwandi; Fikri Rizki Fadlurrahman (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
One of the standards that must be met by sharia hospitals is to provide comprehensive Islamic spiritual services, by all hospital staff, including in nursing services. Determination of Islamic spiritual nursing diagnosis in sharia hospital services is the main thing that must be known by nurses. This study aims to analyze the level of knowledge of nurses in determining the diagnosis of Islamic spiritual nursing care in a Sharia hospital in Bandung, through a correlational research method with a cross sectional approach. The sampling technique used was simple random sampling, a total of 50 adult inpatient nurses who met the inclusion and exclusion criteria. The results showed that the average value obtained by nurses after filling out a questionnaire about determining spiritual nursing diagnoses was 44.16, the level of knowledge of nurses in determining spiritual nursing diagnoses in sharia hospitals was a sufficient category (42%), but on average they were not able to differentiate (C3) definitions between spiritual nursing diagnoses (≥50%). Spiritual care education and training have a close relationship with the knowledge level of nurses, with a significant value <0.0001 and a correlation coefficient of 1.00. The results of the research can be used as a reference for training and further education for nurses so that their knowledge can increase and become basic data for further research. Keywords: Knowledge, Nursing diagnosis, , Spiritual